Zoning of coastal environments based on sediment textural and geochemical characteristics and their major oceanographic constraints: A case study in South Korea. (15th September 2021) - Jung, Hoi-Soo; Lim, Dhongil; Xu, Zhaokai; Kim, Jihun; Lee, Junho; Jeong, Dohyun
Highlights: Coastal zoning aids environmental impact assessment. Sediment textural and geochemical properties are key characters affecting zoning. This (Ahn et al., 2001 ) study applies sediment characters to science-based marine spatial planning. The South Korean coast can be scientifically divided into three zones. The three zones partly coincide with the previous arbitrarily categorized blocks. A primary factor constraining the zoning in this case study is tidal range. Abstract: To assess the environmental impacts of offshore wind farming and sea sand mining, coastal areas are zoned on the basis of their natural oceanographic characteristics. Textural and geochemical properties of South Korean coastal sediments, including mean grain size (Mz), CaCO3 and organic-matter contents, and metal concentrations (Al, K, Ba, rare earth elements, Zr, etc.), were analyzed and categorized in this case study, practically applying common sediment properties for rational zoning of the South Korean coastal environment. Three characteristic zones are scientifically classified in the study area, although four groups of sediment sampling stations were statistically clustered based on their major sediment properties. Zone 1, in the northwestern part of the Korean west coast, is characterized as covered with coarse-grained sediments containing low concentrations of the measured elements under a macro-tidal regime (6.5–9 m), while Zone 3 is characterized by fine-grained sediments with high elemental concentrations under a micro-tidal regime (>3.5 m). Silty Zone 2 sediments appear to be a mixture of sandy Zone 1 and muddy Zone 3 sediments under a meso-tidal regime. The difference in tidal forces among the zones is proposed as a primary constraint of overall sediment textural and geochemical characteristics, while sediment provenance provides subsequent control. Sediment contamination with anthropogenic pollutants is unperceivable in this case study. However, the K and Li concentrations in coarse-grained feldspar and fine-grained illite, respectively, are likely not limited by the tidal flow regime.